Dupilumab in children with eosinophilic esophagitis: a retrospective multicenter study - Mohammed Hasosah; Ghassan Sukkar; Asharf AlSahafi; Ali Zaidan; Nouf Ghous; Abdulmajed Alshahrani; Ziyad Al Zahrani; Naif Hasosah; Mansour Qurashi; Loie Goronfolah; Ali Alsharief; Nagla Kamal (BMC Pediatrics)
Abstract Background Eosinophilic esophagitis (EoE) is a chronic inflammatory disorder characterized by symptoms of esophageal dysfunction and eosinophil-predominant inflammation. Dupilumab is a human monoclonal antibody that targets both IL-4 and IL-13 signaling. It is currently indicated for the treatment of asthma, atopic dermatitis, and EoE. This study aimed to describe children with EoE that is difficult to treat using conventional treatment and to identify symptomatic, histological, and endoscopic improvements after dupilumab treatment. Materials and methods We conducted a retrospective multicenter study in children with confirmed EoE and performed a chart review of patients prescribed dupilumab for EoE. Demographic information, symptoms, and medications including dupilumab treatment were collected. The endoscopic findings, histopathological features, and treatment results were analyzed. We calculated the change in EoE endoscopic reference scoring system (EREFS) scores from the baseline to 3 months. Results Eleven patients were included in this study. The study population comprised seven boys (64%) and four girls (36%). The median age at presentation was 11.6 years (8–13 years). Dupilumab at a dose of 200–300 mg was administered to all patients as second-line therapy for children with EoE refractory to conventional therapy (proton pump inhibitors, corticosteroids, and dietary restrictions). Dupilumab efficacy regarding symptom relief, and endoscopic and histological improvements was 82%, 73%, and 90%, respectively. The mean EoE endoscopic reference scoring system scores changed from a baseline of 6.9 (before dupilumab) to 0.3 (after dupilumab). In addition to the improvement in EoE, the use of corticosteroids in EoE and inhaled corticosteroids in asthma was decreased for all patients, suggesting that dupilumab may be effective in patients with multiple concurrent atopic conditions. Dupilumab had a well-tolerated safety profile, except for one patient who developed conjunctivitis. Conclusion This pediatric study demonstrates the effectiveness of dupilumab as a second-line therapy for symptom relief, and endoscopic and histological improvements of EoE that is refractory to current treatment. A longitudinal, large prospective study is necessary to guide the initiation of dupilumab treatment for childhood EoE, and long-term follow-up data on dupilumab are required. Clinical trial number Not applicable.